Assessment of bone calcium and phosphorus content using micro X‐ray fluorescence spectrometry (μ‐EDXRF): effects of long‐term cadmium poisoning. (13th September 2016) - Cheung, Tsz Wing; Law, Alan Wing Lun; Ahmed, Rafay; Mak, Chun Yu; Lau, Condon
Abstract : This study assesses whether the concentrations of biologically important elements in bones are altered by long‐term consumption of cadmium (Cd)‐contaminated water. Heavy metal poisoning has significant impact on humans, and pollutants such as Cd are often found at high concentrations in waterways. Twelve Sprague Dawley rats consumed water with 50 p.p.m. Cd (Cd group), and another 12 consumed normal water (control group). Six subjects from each group were sacrificed after 2 weeks and the others after 4 weeks. Spectra were acquired from the femur by using the EDAX Eagle III micro‐XRF setup, and quantitative calculations were performed by using the fundamental parameter method to determine the concentrations of elements. A bone calcium/phosphorus concentration ratio (Ca/P) of 2.07 ± 0.001 is observed in the spectra from control subjects after 2 weeks and 2.07 ± 0.001 after 4 weeks. In Cd subjects, Ca/P after 2 weeks is 2.04 ± 0.001 and after 4 weeks is 1.97 ± 0.003. Statistically significant differences are obtained when comparing controls with Cd subjects at both time points and when comparing Cd subjects at both time points. Cadmium poisoning significantly affects bone Ca and P concentrations, increasing the likelihood of osteoporosis and other bone diseases. Copyright © 2016 John Wiley & Sons, Ltd.